Equilibrium real interest rates, secular stagnation, and the financial cycle: Empirical evidence for euro-area member countries - Ansgar Belke; Jens Klose (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
Is the Euro area as a whole, or are individual Euro-area member countries facing a period of sustained lower economic growth, a phenomenon known as secular stagnation? We tackle this question by estimating equilibrium real interest rates and comparing them to actual real rates. Since the financial crisis has altered the degree of leverage in several European economies, we expand our model to incorporate the financial cycle. We estimate the model for the Euro area as a whole and for nine Euro-area member countries. Incorporating the financial cycle changes the estimated equilibrium real interest rates: For some Euro-area member countries, estimates of the equilibrium real interest rate are substantially higher than the standard estimates. In other cases, including our estimates for the Euro area as a whole, the estimated equilibrium real rates are slightly lower than without taking the financial cycle into account but are still higher than the actual rates. This indicates that real monetary policy rates were set even more systematically and consistently below (or not as far above) the natural real rate. Comparing the sequence of actual and equilibrium real rates, only Belgium, France, and Greece are likely to face a period of secular stagnation. – – Liegt vor dem Euro-Raum als Ganzes oder individuellen Mitgliedstaaten eine Periode anhaltend niedrigen Wirtschaftswachstums, ein Phänomen, welches unter dem Namen säkulare Stagnation bekannt ist? Wir widmen uns dieser Frage, indem wir gleichgewichtige Realzinsen schätzen und diese mit den tatsächlichen Realzinsen vergleichen. Weil sich seit der Finanzkrise der Verschuldungsgrad in einigen europäischen Staaten verändert hat, wird das Modell um den Finanzzyklus erweitert. Wir schätzen das Modell für den Euro-Raum als Ganzes und neun Mitgliedstaaten der Währungsunion. Das Hinzufügen des Finanzzyklus ändert die Schätzungen des gleichgewichtigen Realzinses: Für einige Staaten des Euro-Raums werden die Schätzungen des gleichgewichtigen Realzinses so substanziell höher als bei dem Standardansatz. In anderen Fällen, so auch dem Euro-Raum insgesamt, fallen die Schätzungen ein wenig niedriger aus verglichen mit dem Standardmodell. Sie sind aber immer noch höher als die tatsächlichen Realzinsen. Dies impliziert, dass die realen Leitzinssätze systematisch und konsistent unterhalb (oder nicht so weit oberhalb) des gleichgewichtigen Realzinses gesetzt werden. Ein Vergleich der tatsächlichen mit den gleichgewichtigen Realzinsen zeigt, dass sich nur Belgien, Frankreich und Griechenland in eine Phase säkularer Stagnation befinden könnten.
Keywords: E43; F45; C32; 330; equilibrium real interest rate; Euro area; financial cycle; heterogeneity; monetary policy; secular stagnation